Light weight exterior body parts for vehicle and composite used thereof. - Yunus, Robiah; Rezaei, Fateme; Ibrahim, Nor Azowa (2007)

(untitled)
An article for assembling vehicle exterior body parts made of composite comprises a matrix of polypropylene; and carbon fibers having length of 5mm to 15mm in a weight percentage of 7 to 15 forming a discontinuous phase within matrix of polypropylene.